Primary Epstein-Barr virus infection in 2-year-old children: report of 3 cases - Wan, Kong-Sang; Yu, Yi-Jung; Wu, Wei-Fong (The Turkish Journal of Pediatrics, 2010)
Some children less than four years old have Epstein-Barr virus (EBV)-induced infectious mononucleosis (IM). Because primary EBV infection in infants and young children is usually asymptomatic or subclinical, EBV infection diagnosis may not be easy among young children. To illustrate the clinical characteristics and diagnostic procedures for EBV infection in young children, the authors report herein three cases of primary EBV infection in two-year-old children with an evaluation of their initial clinical symptoms. The results showed that the common initial clinical manifestations are puffy eyelids and hepatosplenomegaly, and that these signs suggest a tentative diagnosis of IM. In conclusion, EBV capsid immunoglobulin (Ig)M antibodies and atypical lymphocytes are useful diagnostic measurements in very young children with symptoms suggestive of IM.